The Cannabinoid Receptor Agonist WIN 55212-2 Inhibits Neurogenic Inflammations in Airway Tissues - Shigemi Yoshihara; Hiroshi Morimoto; Makoto Ohori; Yumi Yamada; Toshio Abe; Osamu Arisaka (Elsevier, 2005)
We examined the effects of a cannabinoid receptor agonist, (R)-(+)-[2,3-dihydro-5-methyl-3-[(4-merpholino)methyl]pyrrolo-[1,2,3-de]-1,4-benzoxazin-6-yl](1-naphthyl)methanone (WIN 55212-2), on various respiratory reactions induced by the activation of capsaicin-sensitive afferent sensory nerves (C-fibers). WIN 55212-2 significantly inhibited capsaicin-induced guinea pig bronchoconstriction, but not the neurokinin A-induced reaction. Intravenous injection of WIN 55212-2 also blocked cigarette smoke-induced rat tracheal plasma extravasation. However, substance P-induced rat tracheal plasma extravasation was not affected by the administration of WIN 55212-2. A cannabinoid CB2 receptor antagonist, {N-[(1S)-endo-1,3,3-trimethylbicyclo[2.2.1] heptan-2-yl]-5-(4-chloro-3-methylphenyl)-1-(4-methylbenzyl)pyrazole-3-carboxamide} (SR 144528) reduced the inhibitory effects of WIN 55212-2, but not a cannabinoid CB1 antagonist, [N-(pipe-ridin-1-yl)-5-(4-chlorophenyl)-1-(2,4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamidehydrochloride] (SR 141716A). A Maxi-K+ channel opener, 1-(2'-hydroxy-5'-trifluoromethylphenyl)-5-trifluoromethyl-2(3H)benzimidazolone (NS 1619), specifically inhibited capsaicin-induced guinea pig bronchoconstriction and cigarette smoke-induced rat tracheal plasma extravasation. These findings suggest that WIN 55212-2 inhibits the activation of C-fibers via cannabinoid CB2 receptors and Maxi-K+ channels and reduces airway neurogenic inflammatory reactions in vivo. Keywords:: cannabinoid, C-fiber, bronchoconstrictoin, plasma extravasation, Maxi-K+ channel